Analisis Desentralisasi Fiskal di Kabupaten Bungo - Supriyadi Supriyadi; Arman Delis; Selamet Rahmadi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2013)
The purpose of this study was to measure and analyze the degree of fiscal decentralization in Bungo district during the years 2000 to 2010 as well as analyzing the relationship of GDP to the degree of fiscal decentralization during the same period. The results of this study indicate that the degree of fiscal decentralization PAD average of only 9.247, which means much less, then the Tax Revenue and Non Tax even though the degree of fiscal decentralization is higher in the amount of 10.434, but still lacking in the category. Furthermore, to donations / aid from the Provincial and Local Grants instead showed a lower value of the degree of fiscal decentralization of local revenue, which amounted to only 3.187 (much less). This indicated that the District Government of Bungo still very large dependence on the Central Government. It is also indicated by the high ratio of financial dependency Bungo Regency on income transfers from the central government which is an average of 87.57%. The study also showed that the association of GDP with the degree of fiscal decentralization component of revenue (PAD) is negative (-0.180). Further to the relationship of GDP to fund components of the degree of fiscal decentralization Tax Revenue and Non-Tax showed a positive relationship with a value of 0.715. While GDP relationship with the degree of fiscal decentralization component Donations / aid from the Provincial and Local Grants are also positively related to the value of 0.648.Keywords: decentralization, fiscal decentralization